PENGARUH SUBSTITUSI TEPUNG KIMPUL (Xanthosomasagittifolium) TERHADAP TINGKAT PENGEMBANGAN DAN DAYA TERIMA BOLU - Faresia Milda Kumara; Eni - Purwani (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
The lack of utilization of local food one of which is kimpul (Xanthosomasagittifolium). Processed into flour is one of the methods for kimpul so it can be utilized into various food products such as cake. Kimpul has no gluten content such as wheat flour so it affects the expansion level and sensory preferences of the cake.The purpose of this study was toknow the relation of substitution ofkimpulflour to the expansion level and sensory preferences of cake. This research isusing an experimental study. The object used in this research is cake with 0%; 12.5%; 25%; 37.5% substitution of kimpul flour. Panelists used in this study were 33 panelists. What is assessed are the expansion level of cake from each substitution and the sensory preferences includes color, aroma, taste, texture and overall by the panelists. The analysis of the expansion level of cake by substitution of kimpul flour was done using one way Anova test, while for the sensory preferences using Friedman test and Duncan test.This study shows the best cake cultivation rate is cake with  12.5% of kimpul flour substitution with an average of 88.56% followed by cake with 25% of kimpul flour substitution with an average of 85.82%. In the overall sensory preferences test,most of panelists prefercake with 0% of kimpul flour substitution and followed by cake with 12.5% of kimpul flour substitution. This study can be concluded thatthere are no effects ofkimpul flour substitution on the expansion level of the cake, and there are effects of kimpul flour substitution on the sensory preferences test of the cake.